Creating Vignettes of Early Onset Dementia: An Exercise in Public Sociology. (February 2016) - Jenkins, Nicholas; Keyes, Sarah; Strange, Liz
Drawing on core principles of public sociology, this article discusses the creation of four theatrical vignettes about living with early onset dementia (symptoms of dementia pre-65). The vignettes were developed through an Image Theatre workshop, involving families living with early onset dementia. They were designed to capture key themes, issues and experiences that emerged from the group's collective experience. While the content of the vignettes speaks to a range of key sociological debates (especially in relation to the lived experience of time, risk, social exclusion and stigma in dementia) the process of creating and using the vignettes represents the first empirical application of a (public) sociological approach to 'person-centredness' in dementia; which views persons as 'dividual' and selves as transactive. We conclude by advocating for a rich and diverse public sociology of dementia in the 21st century.